2008
DOI: 10.1128/iai.00741-07
|View full text |Cite
|
Sign up to set email alerts
|

The Acute-Phase Reactant C-Reactive Protein Binds to Phosphorylcholine-ExpressingNeisseria meningitidisand Increases Uptake by Human Phagocytes

Abstract: Neisseria meningitidis is a global cause of meningitis and septicemia. Immunity to N. meningitidis involves both innate and specific mechanisms with killing by serum bactericidal activity and phagocytic cells. C-reactive protein (CRP) is an acute-phase serum protein that has been shown to help protect the host from several bacterial pathogens, which it recognizes by binding to phosphorylcholine (PC) on their surfaces. Pathogenic Neisseria species can exhibit phase-variable PC modification on type 1 and 2 pili.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…2D). Taken together, these results indicate that the CPS of E. rhusiopathiae is modified by PCho, as has been shown for other mucosal pathogens, including N. meningitidis, S. pneumoniae, and H. influenzae (5,31,33). The pooled CPS-containing fractions were further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…2D). Taken together, these results indicate that the CPS of E. rhusiopathiae is modified by PCho, as has been shown for other mucosal pathogens, including N. meningitidis, S. pneumoniae, and H. influenzae (5,31,33). The pooled CPS-containing fractions were further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…1). The acute phase response element C-reactive protein (CRP), which binds PCho and can be bactericidal in the presence of complement, inhibits the PAFr/PCho interaction in vitro and in vivo [24, 25]. Similarly, surfactant, which is rich in PCho, and antibody to phosphorylcholine are competitive inhibitors of ligand binding to PAFr and CRP in the lungs [26].…”
Section: Common Doorway To Invasionmentioning
confidence: 99%
“…Furthermore, CRP has been reported to display anti-inflammatory effects in monocytes through down-regulation of alpha2-macroglobulin expression and up-regulation of liver X receptor expression (Hanriot et al, 2008). CRP was found to bind to a ligand on Leishmania donovani and phosphorylcholine-expressing Neisseria meningitides, and hence increase their uptake by human phagocytes (Culley et al, 1996, Casey et al, 2008. Thomas-Rudolph et al (2007) have also reported that innate recognition by CRP enhances effective uptake and presentation of bacterial antigens through Fc-gamma receptors on dendritic cells and stimulates protective adaptive immunity.…”
Section: In Vitromentioning
confidence: 99%